The Identity That Doesn’t Deny Difference: A Non-dualist Argument - Guha N. (My University, 2025)
Brahmānanda Sarasvatī has written an elaborate comment on the following inference cited in Advaitasiddhi: attribute etc. are identical to and different from attributee etc. since they are co-referential. There he wants to prove that every significant case of attribution (such as ‘x [is] y’) is a case of identity that coexists with a difference between two demarcators (upalakṣaṇa). The identity that coexists with difference is called ‘equality’ (tādātmya). This paper will argue that in each case of equality, the realist ontology chooses either identity over difference or the reverse. In the case of ‘the black pot’, the realist ontology prefers difference over identity. In the case of ‘the qualified object is the mere object’, the same ontology prefers identity over difference. Accordingly the ontological ‘entity’ gets projected. This is perhaps because the realist ontology is guided by Ockham’s razor and the grammatical classification of objects. © 2021, The Author(s), under exclusive licence to Springer Nature B.V.